Model Pengendalian Katodik Dalam Elektrode Disk Pemutar Sistem Korosi - Isni Utami (Jurnal Teknik Industri, 2011)
The effect of fluids flow rate onto necessity of current density cathodic protection which characterized using Rotating disk electrode (RDE) model has been researched on an electrochemistry manner. This research was done to AISI 1018 steel as the electrode spinning cylinder-shaped inside aerated dissolvable NaCl 3.5%. using variation spinning rate 0–2000rpm and 25–75° C temperature. Current density cathodic protection necessity determined from the steel interface potential - 800mV with reference anode Ag/AgCl. Experiment result shows that the increasing of electrode rate, cathodic protection current density needs increased due to diffusion layer tare faction and also because corrosion potential become more positive. Higher temperature would increase cathode protection current density needs and makes corrosion potential more negative. Oxygen activation energy value to be diffused onto electrode surface support the corrodibility AISI 1018 toward temperature increment, because cathodic reaction controlled by transfer mass of dissolved oxygen.